2020
DOI: 10.31234/osf.io/czskd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dispositional and situational attribution of COVID-19 risk: A content analysis of response typology (Version: 1)

Abstract: Pre-Peer Review Version 1: In the current COVID-19 pandemic, there have been official health recommendations of social distancing, thorough handwashing, and self-isolation to prevent the spread of the virus. However, compliance with these recommendations has been mixed. We suggest that non-compliance may be justified by one’s (mis)perception of their own COVID-19 risk. In this paper, we explore the dispositional and situational attribution of self-reported COVID-19 risk, as per Heider’s Attribution Theory. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…For example, emerging research has suggested that greater anxiety and perceived lack of control were significantly associated with belief in COVID-19 conspiracy theories in an online sample of Slovak adults ( Srol et al, 2020). It may also be useful to include measures of other relevant psychological constructs, such as perceived risk (see Dunning & Pownall, 2020) and support for governmental responses to pandemic crises (e.g., Conway et al, 2020), to better account for some of our hypothesizing. Of course, it should also be noted that the present research was centrally focused on psychological factors that are associated with compliance, but individual ability and willingness to comply with social-distancing measures are also likely to be affected by economic, sociopolitical, and temporal factors (e.g., Atchison et al, 2020;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, emerging research has suggested that greater anxiety and perceived lack of control were significantly associated with belief in COVID-19 conspiracy theories in an online sample of Slovak adults ( Srol et al, 2020). It may also be useful to include measures of other relevant psychological constructs, such as perceived risk (see Dunning & Pownall, 2020) and support for governmental responses to pandemic crises (e.g., Conway et al, 2020), to better account for some of our hypothesizing. Of course, it should also be noted that the present research was centrally focused on psychological factors that are associated with compliance, but individual ability and willingness to comply with social-distancing measures are also likely to be affected by economic, sociopolitical, and temporal factors (e.g., Atchison et al, 2020;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have investigated this construct in different populations during the COVID-19 pandemic, showing interesting results. For instance, Dunning and Pownall [42] investigated the link between perceived risk of being personally infected and health locus of control in a British sample.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, emerging research has suggested that greater anxiety and perceived lack of control were significantly associated with belief in COVID-19 conspiracy theories in an online sample of Slovak adults (Šrol et al, 2020). It may also be useful to include measures of other relevant psychological constructs, such as perceived risk (see Dunning & Pownall, 2020) and support for governmental responses to pandemic crises (e.g., Conway et al, 2020), to better account for some of our hypothesising. Of course, it should also be noted that the present research was centrally focused psychological factors that are associated with compliance, but individual ability and willingness to comply with social-distancing measures are also likely to be affected by economic, socio-political, and temporal factors (e.g., Atchinson et al, 2020;Zhang et al, 2020).…”
Section: Covid-19 15mentioning
confidence: 99%